Erratum to chapter 10, ‘Tendon stem cell niche’ - Almeida, Raquel Costa (2016)
In Chapter 10, the Table of Contents, and the Contributors List, the lead author’s last name was misspelled ‘Costa-Alameida’; it should have been spelled ‘CostaAlmeida’.